2007
DOI: 10.1007/s10658-007-9166-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of late blight in organic potato production: evaluation of copper-free preparations under field, growth chamber and laboratory conditions

Abstract: In order to replace copper fungicides in organic potato production, 53 copper-free preparations (CFPs) based on natural compounds, including plant extracts and microorganisms, and five copper preparations were evaluated for their potential to control Phytophthora infestans, the pathogen that causes late blight of potatoes. In in vitro assays, 30% of the CFPs inhibited indirect germination of sporangia, 26% mycelial growth and in growth chamber experiments, 21% efficiently reduced foliar blight of tomato plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…II). This corresponds to results of other studies which have demonstrated the efficacy of natural products in reducing leaf infestation on potato and tomato by P. infestans (Blaeser and Steiner, 1999;Quintanilla et al, 2002;Dorn et al, 2007;Wang et al, 2007). None of the plant extracts controlled disease as well as Ridomil Plus and Plantineb.…”
Section: Inhibition Of P Infestans On Whole Tomato Plants In the Gresupporting
confidence: 88%
See 1 more Smart Citation
“…II). This corresponds to results of other studies which have demonstrated the efficacy of natural products in reducing leaf infestation on potato and tomato by P. infestans (Blaeser and Steiner, 1999;Quintanilla et al, 2002;Dorn et al, 2007;Wang et al, 2007). None of the plant extracts controlled disease as well as Ridomil Plus and Plantineb.…”
Section: Inhibition Of P Infestans On Whole Tomato Plants In the Gresupporting
confidence: 88%
“…Quintanilla et al (2002) demonstrated that the essential oil of Hyssopus officinalis could inhibit the mycelial growth of P. infestans and suppress late blight on potato plants in growth chambers. Extracts from Potentilla erecta, Salviae officinalis (Blaeser and Steiner, 1999;Dorn et al, 2007), Galla chinensis and Rheum rhabarbarum (Wang et al, 2007) have also shown promising effects against potato late blight.…”
Section: Introductionmentioning
confidence: 99%
“…Various copper compounds are recommended and are widely used for control of plant diseases caused by bacteria as well (Janse, 2005). Even organic agriculture still relies on copper for control of some diseases (Dorn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Myco-Sin®VIN was ineff ective to control grey mould in 2011, when rainfall period occurred in the end of April during strawberry fl owering, perhaps because it could be washed away from the leaf surface. This assumption is based on the experience of Michelante and Haine (2004) and Dorn et al (2007), who noted Myco-Sin (very similar product to Myco®Sin VIN) was eff ective to reduce Phytophthora infestans in potatoes in in vitro assay, but it showed signifi cantly lower effi cacy in fi eld conditions. The authors supposed the failure under fi eld conditions due to a lack of stability (sulfuric clay showed poor rainfastness) under prevailing environmental conditions and not to a lack of effi cacy.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce or replace copper fungicides not only in organic production, sulfuric clays are tested to control pathogens (Dorn et al, 2007;Michelante and Haine, 2004). In organic growing sulfuric clays are successfully introduced into the protection strategies, mainly in apples (Jamar and Lateur, 2007;Jamar et al, 2010;Kelderer et al, 2010;Kunz et al, 2011;Falta and Vávra, 2010).…”
mentioning
confidence: 99%